COMPARATIVE ADVANTAGE MEASUREMENT IN ASEAN’S TEN LEADING EXPORT COMMODITIES: A CASE STUDY OF ASEAN-5 - Estira Woro Astrini; Nurul Azizah Az zakiyyah (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This paper analyzed ASEAN-5’s comparative advantage of their best ten products using “products mapping” as now we faced ASEAN Economic Community (AEC). Its a need to know which commodities are those countries in comparative advantage and as a net exporter. Using data retrieved from UN COMTRADE accessed from INTRACEN website, we used information of best ten ASEAN’s leading export commodities which was under 2 digits HS classsification. For analysis in this paper, we derived those products into 4 digits HS classification, so then we were not only use 10 commodities but 320 commodities. Comparative advantage measurement that we used were Revealed Symmetric Comparative Advantage (RSCA), as for know if the countries were net-importer or net-exporter we used Trade Balance Index (TBI). Lastly, we combined those two indexes of comparative advantage to draw each country’s products mapping. From the analysis, we got the result that, Indonesia’s exported commodities (net-exporter) and comparative advantage mostly are from animal or vegetable fats and oil, Malaysia’s mostly are from rubber and articles thereof, Singapore and Thailand’s mostly from organic chemicals, and Philipines’s mostly from electrical and electrical equipment.